(untitled) (Proceedings of the International Conference on Agriculture, 2023)
Trichoderma sp. is a well-known biocontrol agent of Ganoderma basal stem rot (BSR) disease in oil palms. A lot of commercial products containing the beneficial microbe are available around the world. PalmaShield, containing Trichoderma asperellum (M103), is one of the commercialized and marketed products in Malaysia by FGV Agri Services Sdn. Bhd. M103 has already been proven to suppress Ganoderma growth in in-vitro studies by causing more than 85% inhibition of radial growth and has reduced more than 50% of BSR disease infections at the nursery stage. The journey to mass produces the M103 requires optimization of the fermentation process and maintaining the stability of the final product. For the fermentation process, the physical parameters were tested. M103 can grow well in submerged fermentation with an initial pH of 3, an incubation temperature between 28 and 30°C, a shaker speed of 150 rpm, and an inoculum size of 2 to 3% v/v. The culture broth from the fermentation process is mixed with clay for the development of powder formulations. During the final stage, continuous contamination of the final product in storage would be challenging. The moisture content of the final product was found to be the critical parameter to be controlled to eliminate the risk of bacterial contamination and maintain the viability of M103. Therefore, several drying techniques were studied, and product stability was monitored for 1 year. These findings provide important parameters to be controlled during the production process of Trichoderma’s product in powder form.